Cognitive load in cyclists while navigating in traffic: Effects of static and dynamic route events on neural activity of cyclists measured by fNIRS - Mehmet Baran Ulak; Fenja Heine; Aykut Eken; Pookhao Chinpongsuwan; Mario Boot; Karst T. Geurs; Funda Yildirim (PLoS ONE, 2025)
Increased cognitive load during cycling can lead to safety issues, particularly during complex situations such as participating in motorised traffic or manoeuvring at intersections. Understanding the patterns of cognitive activity in cyclists across various events can provide valuable insights into cyclists’ cognitive load. Therefore, this study aims to investigate when cyclists undergo cognitive load changes during cycling and how these changes manifest in neural activity and connectivity. For this purpose, we analysed neural activity data collected during a real-life field experiment by a non-invasive portable method, namely Functional Near-Infrared Spectroscopy (fNIRS), sensitive to neural activity in the prefrontal cortex region. Findings indicate differences in cognitive load, as shown by varying oxygenation levels, during both static (i.e., presence of traffic lights, intersections, roundabouts, or crosswalks) and dynamic (i.e., presence of motorised vehicles, cyclists, pedestrians, or avoiding objects) route events. Neural activity patterns highlight how different road events elicit varying cognitive and neural demands in cyclists. Events like intersections and pedestrian encounters show dense connectivity, particularly in regions related to decision-making, attention, and motor planning, implying a high cognitive load on cyclists. Roundabouts and traffic light scenarios demonstrate intermediate connectivity, indicating the need for adaptive attention and action selection. This study contributes to understanding the underlying cognitive mechanisms during cycling in real-life conditions and the neural markers that can identify different route events encountered while cycling.